Identifikasi Kebutuhan Infrastruktur Penunjang Pengembangan Pariwisata di Wilayah Perbatasan Utara Kalimantan - Efraim Bavo Priyana; Eko Prihartanto (Borneo Engineering : Jurnal Teknik Sipil, 2021)
Tourism as a support for the economy of a region requires special attention to attract tourists both from home and abroad. Nunukan Regency as an area directly adjacent to the State of Malaysia still lacks infrastructure. The need for supporting infrastructure adds to the attractiveness of a tourist area. So to know what are the needs of tourist areas need to be done research by identifying.The research method used is descriptive statistics with respondents from Stakeholders in Nunukan Regency, data obtained by the dissemination of questionnaires and interviews. This research object is a potential tourist area as well as tourist attractions in Nunukan Regency.The results that have been obtained from this study there are 3 variables including Access, accommodation, Facilities with a total of 17 indicators. Where there are 3 invalid indicators such as the existence of roads through land transportation, the existence of places of worship, passive recreational facilities (Seating, campfires). Identification obtained with a percentage value of 85% is available facilities to enjoy the beauty of nature, this is because the dominant tourism in Nunukan Regency is Natural Beauty.